Synthesis report 2024 on co-designing agroecology innovations for Lao PDR - Smith, B.; Douangsavanh, Somphasith; Dubois, Mark (International Water Management Institute, 2024)
The agroecology living landscape (ALL) in Attapeu province, Lao PDR, represents a significant initiative aimed at promoting agroecological transitions through innovative water management, crop diversification, and community-driven practices. Situated in the southern part of Laos, Attapeu is characterised by a diverse landscape, whose population is primarily engaged in subsistence farming. This report explores the implementation of key agroecological practices within two primary sites in the province: Ban Inthee and Nong Lom. In 2023, six key initiatives were identified that could support both environmental and socioeconomic sustainability in the region: i) solar powered groundwater pumping; ii) ricefish systems; iii) organic red-rice cultivation, iv) wetlands management; v) soil improvement, and vi) gender action learning. This report details the methods used to implement these initiatives, highlighting the importance of participatory approaches and collaboration with local communities. The report then evaluates the results of these initiatives, and their contribution to key agroecological principles including diversity, efficiency, resilience, and cultural relevance. The outcomes demonstrated positive environmental impacts, including improved soil health, enhanced biodiversity, and more efficient use of water resources. Socially, the initiatives empowered women and fostered inclusive decision-making, while economically, they contributed to food security and diverse livelihoods. The report concludes with recommendations for scaling up these practices, emphasising the need for infrastructure investment, capacity building, and long-term monitoring to ensure sustainability.